THE EFFECT OF PROFITABILITY, LEVERAGE, AND OPERATING COSTS ON CORPORATE INCOME TAX EXPENSE PAYABLE ON CONSTRUCTION COMPANIES PERIOD 2014-2023: THE EFFECT OF PROFITABILITY, LEVERAGE, AND OPERATING COSTS ON CORPORATE INCOME TAX EXPENSE PAYABLE ON CONSTRUCTION COMPANIES PERIOD 2014-2023 - Putri, Risza Estuning Puspita; Kusumastuti, Sri Yani (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study aims to estimate the effect of profitability, leverage, and operating costs on corporate income tax payable in construction companies listed on the Indonesia Stock Exchange for the period 2014 - 2023. This research uses a quantitative approach method. Based on the purposive sampling method, researchers obtained 4 sample companies of construction companies with a total observation data of 40 data. The data analysis technique used in this research is panel data regression analysis with the help of Eviews9. The results of this study indicate that partial profitability and operating costs have a positive effect on corporate income tax, while leverage has a negative effect on corporate income tax.